SOCIOCULTURAL PRACTICE FAIRCLOUGH DALAM PEMBERITAAN KASUS PENGANIAYAAN PRADA LUCKY DI CNN INDONESIA - Thoriq Al Sajjad, Muhammad; Permata Raharjo, Resdianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The death of Private Lucky in the Indonesian National Armed Forces (TNI) has drawn attention due to issues of seniority, internal violence, and the image of the military institution. The media plays a role in constructing reality through the news coverage it presents. This study aims to examine the discourse surrounding the abuse of Private Lucky in CNN Indonesia’s online media and to identify how situational, institutional, and social levels influence the construction of meaning in news texts. The research data consists of CNN Indonesia news articles from August 2025 related to the case of Private Lucky’s abuse. Data was collected through documentation and analyzed using an objective hermeneutic model via a sequential and detailed analysis. The results of the study indicate that, in the dimension of sociocultural practices, the coverage of Prada Lucky’s abuse case reflects criticism of the culture of seniority, the potential for impunity, and the importance of the principle of equality before the law. Thus, CNN Indonesia’s coverage not only conveys information but also constructs a discourse that emphasizes Prada Lucky’s circumstances, legal transparency, and the demand for justice within the military institution.